Will potential entry to European Union impact future of the fishing industry in Iceland? - Malgorzata Katrín Molenda 1988- (2012)
The purpose of this essay is to look into possible impact if membership of the European Union on the Icelandic fishing industry. The research looked in to impact of the investment, employment and trade effects in the Icelandic fish sector. The crisis in 2008 has changed Icelandic attitude towards European Union. Icelandic politics used to be more sceptical about European Union but after the crisis more politicians started to look at Icelandic accession to the European Union in more positive way. Iceland applied to join EU on 16th July 2009. In that contest it is important to remember that Iceland is already integrated to the EU market trough the EEA agreement. Fisheries are one of the most important Icelandic resources because of their trade value.